Killing the legends : the lethal danger of celebrity [large type] - O'Reilly, Bill; Dugard, Martin (O'Reilly, Bill. Killing series, 2022)
"The King is dead. The Walrus is shot. The Greatest is no more. Elvis Presley, John Lennon, and Muhammad Ali. These three icons changed not only the worlds of music, film, and sports, but the world itself. Their faces were known everywhere, in every nation, across every culture. And their stories became larger than life--until their lives spun out of control at the hands of those they most trusted... explore[s] the lives, legacies, and tragic deaths of three of the most famous people of the 20th century. Each experienced immense success, then failures that forced them to change; each faced the challenge of growing old in fields that privilege youth; and finally, each became isolated, cocooned by wealth but vulnerable to the demands of those in their innermost circles"--